2016
DOI: 10.1111/hdi.12471
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 18 F‐FDG PET/CT scan to diagnose the etiology of fever of unknown origin in patients on dialysis

Abstract: The present study is first study of 18F-FDG PET/CT scan in patients of end stage renal disease on dialysis with FUO. The study showed that the 18 F FDG PET/CT scan may present an opportunity to attain the diagnosis in end stage renal disease patients on dialysis with FUO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…In patients with FUO, FDG PET and other nuclear imaging techniques can be the differentiator in finding the source of infection. In one study on 20 patients with ESRD with FUO, FDG PET scans revealed areas of increased FDG uptake in 15 patients [12]. Of the 20 patients, 19 had a change in treatment to address the fever [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with FUO, FDG PET and other nuclear imaging techniques can be the differentiator in finding the source of infection. In one study on 20 patients with ESRD with FUO, FDG PET scans revealed areas of increased FDG uptake in 15 patients [12]. Of the 20 patients, 19 had a change in treatment to address the fever [12].…”
Section: Discussionmentioning
confidence: 99%
“…In one study on 20 patients with ESRD with FUO, FDG PET scans revealed areas of increased FDG uptake in 15 patients [12]. Of the 20 patients, 19 had a change in treatment to address the fever [12]. Gallium 67 citrate and labeled WBC scanning are often compared to FDG PET.…”
Section: Discussionmentioning
confidence: 99%
“…PET‐CT is a dual modality imaging consisting of a PET scanner and an x‐ray CT scanner. The use of PET‐CT to identify sepsis has been described in many settings . However, to our knowledge, the diagnosis of occult infection in a non‐functioning kidney transplant with PET‐CT has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Infections are the most common cause for fever of unknown origin (FUO) 1. Tuberculosis (TB), particularly extra pulmonary TB (EPTB) is not an uncommon cause for FUO especially in the tropical countries 2. Genitourinary TB (GUTB) is one of the common sites for EPTB, although the estimates are variable 3 4.…”
Section: Introductionmentioning
confidence: 99%